Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.29228/ijlet.54130
|View full text |Cite
|
Sign up to set email alerts
|

Göç Ve Göçmenli̇k Konularini Ele Alan Çocuk Edebi̇yati Eserleri̇ Üzeri̇ne Bi̇r İnceleme

Abstract: In this research, in the works titled "My Name Is Nobody", " When Hitler Stole Pink Rabbit ", "If I Were a Bird, If I Fly Home" and "The Little Immigrant", which deal with the subject of immigration and immigration, it is aimed to convey the aspects of these subjects to the reader and how the works are suitable for children and children. It is aimed to determine whether it is tr ue to reality or not. In the study, document analysis, which is one of the qualitative research methods, was used and content analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…Similar to the feeling of "longing" that we encounter in the new place/new life cycle of migrant children in the books examined, Altunbay-Çakır (2018) also found that the characters in the works had a great longing for their homeland in their studies in which they examined the works dealing with the subject of war and migration. In the new place/new life cycle, similar to the works of Çelik-Göre (2021), marginalization, fear, anxiety and similar to Yürek's (2016) study, elements of language, longing, and incompatibility were observed.…”
Section: Extended Summarysupporting
confidence: 74%
See 1 more Smart Citation
“…Similar to the feeling of "longing" that we encounter in the new place/new life cycle of migrant children in the books examined, Altunbay-Çakır (2018) also found that the characters in the works had a great longing for their homeland in their studies in which they examined the works dealing with the subject of war and migration. In the new place/new life cycle, similar to the works of Çelik-Göre (2021), marginalization, fear, anxiety and similar to Yürek's (2016) study, elements of language, longing, and incompatibility were observed.…”
Section: Extended Summarysupporting
confidence: 74%
“…Göç teması kapsamında ele alınan çocuk kitaplarının duyarlık eğitimi kapsamında (Melanlıoğlu 2020b), sosyolojik bağlamda (Balta 2018), savaş ve göç açısından (Altunbay-Çakır 2018), mülteci kahramanların yaşadıkları çatışmalar doğrultusunda (Melanlıoğlu 2020a; Yiğittürk Ekiyor 2021) ele alındığı çalışmalar alanyazında bulunmaktadır. Göç ve göçmenliği ele alan çocuk kitaplarında bu konuların hangi yönleriyle ele alındığı da incelenmiştir (Çelik-Göre 2021). Ayrıca çocuk kitaplarının farklı açılardan incelendiği (Bayram 2019; Güran Yiğitbaşı 2018) çalışmalar da bulunmaktadır.…”
Section: Introductionunclassified